Front Cover: Numerical demonstration of a transactive energy trading model for microgrids. Issue 4 (16th March 2022) - Crasta, Cletus; Mishra, Sambeet; Agabus, Hannes; Palu, Ivo; Wen, Fushuan
Abstract : The cover image is based on the Case Study Numerical demonstration of a transactive energy trading model for microgrids by Cletus Crasta et al., https://doi.org/10.1049/rpg2.12431 .